Mechanisms of pathological scarring: Role of myofibroblasts and current developments - Sarrazy, Vincent; Billet, Fabrice; Micallef, Ludovic; Coulomb, Bernard; Desmoulière, Alexis (Wound repair and regeneration, 2011)
ABSTRACT Myofibroblasts play a key role in the wound‐healing process, promoting wound closure and matrix deposition. These cells normally disappear from granulation tissue by apoptosis after wound closure, but under some circumstances, they persist and may contribute to pathological scar formation. Myofibroblast differentiation and apoptosis are both modulated by cytokines, mechanical stress, and, more generally, cell–cell and cell–matrix interactions. Tissue repair allows tissues and organs to recover, at least partially, functional properties that have been lost through trauma or disease. Embryonic skin wounds are repaired without scarring or fibrosis, whereas skin wound repair in adults always leads to scar formation, which may have functional or esthetic consequences, as in the case of hypertrophic scars, for example. Skin wound repair involves a precise remodeling process, particularly in the dermal compartment, during which fibroblasts/myofibroblasts play a central role. This article reviews the origins of myofibroblasts and their role in normal and pathological skin wound healing. This article focuses on traumatic skin wound healing, but largely, the same mechanisms apply in other physiological and pathological settings. Tissue healing in other organs is examined by comparison, as well as the stromal reaction associated with cancer. New approaches to wound/scar therapy are discussed.